2017
DOI: 10.1016/j.niox.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase and structure-based inhibitor design

Abstract: Once it was discovered that the enzyme nitric oxide synthase (NOS) is responsible for the biosynthesis of NO, NOS became a drug target. Particularly important is the over production of NO by neuronal NOS (nNOS) in various neurodegenerative disorders. After the various NOS isoforms were identified, inhibitor development proceeded rapidly. It soon became evident, however, that isoform selectivity presents a major challenge. All 3 human NOS isoforms, nNOS, eNOS (endothelial NOS), and iNOS (inducible NOS) have nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…Note that recent studies, using both single cell genomic methods as well as immunohistochemistry, have shown that some cortical neurons express eNOS (Yousef et al, 2004;Lein et al, 2007;Tasic et al, 2016), and that some endothelial cells of cerebral arterioles express nNOS (Vanlandewijck et al, 2018;Zeisel et al, 2018), so the endothelial/neural specificity of these enzymes is not complete. Additionally, crystal structures and careful pharmacology experiments have revealed that 'selective' pharmacological inhibitors of nNOS are much less selective than was originally thought (Bland-Ward and Moore, 1995;Reiner and Zagvazdin, 1998;Engelhardt et al, 2006;Pigott et al, 2013;Poulos and Li, 2017), so it is likely that there are no inhibitors of nNOS or eNOS are specific enough to target one enzyme over another in vivo. Finally, locomotion-evoked dilations are unlikely to be mediated by eNOS expressed in endothelial cells as increases in eNOS activity in response to flow-evoked changes in diameter evolve over minutes, not seconds (Kim et al, 2016) (too slow to account for the locomotion-evoked dilations), and there are no shear-stress changes seen with sensory-evoked dilation (Ngai and Winn, 1996).…”
Section: Nnos-expressing Neurons and No Signaling Control Arterial DImentioning
confidence: 99%
“…Note that recent studies, using both single cell genomic methods as well as immunohistochemistry, have shown that some cortical neurons express eNOS (Yousef et al, 2004;Lein et al, 2007;Tasic et al, 2016), and that some endothelial cells of cerebral arterioles express nNOS (Vanlandewijck et al, 2018;Zeisel et al, 2018), so the endothelial/neural specificity of these enzymes is not complete. Additionally, crystal structures and careful pharmacology experiments have revealed that 'selective' pharmacological inhibitors of nNOS are much less selective than was originally thought (Bland-Ward and Moore, 1995;Reiner and Zagvazdin, 1998;Engelhardt et al, 2006;Pigott et al, 2013;Poulos and Li, 2017), so it is likely that there are no inhibitors of nNOS or eNOS are specific enough to target one enzyme over another in vivo. Finally, locomotion-evoked dilations are unlikely to be mediated by eNOS expressed in endothelial cells as increases in eNOS activity in response to flow-evoked changes in diameter evolve over minutes, not seconds (Kim et al, 2016) (too slow to account for the locomotion-evoked dilations), and there are no shear-stress changes seen with sensory-evoked dilation (Ngai and Winn, 1996).…”
Section: Nnos-expressing Neurons and No Signaling Control Arterial DImentioning
confidence: 99%
“…However, l-NAME is not a specific NOS inhibitor; rather, it weakly inhibits all types of NOS and can even release NO. [79][80][81] Therefore, the above statement needs to be strengthened by further studies using a selective eNOS inhibitor. It is worth noting that different opinions exist regarding the role of eNOS in pulp flow.…”
Section: Anmentioning
confidence: 99%
“…However, they suffer of major limitations in terms of accuracy and the capability to account for highly flexible and conformationally heterogeneous proteins. The interaction of NOSs with selective inhibitors has been reported [ 47 , 48 ] but there has been no extensive computational investigation of the free enzyme structure.…”
Section: Nos Structurementioning
confidence: 99%